A comprehensive review of the lipid cubic phase or in meso method for crystallizing membrane and soluble proteins and complexes. Issue 1 (1st January 2015) - Caffrey, Martin
<x xml:space="preserve">Abstract</x> The lipid cubic phase or in meso method is a robust approach for crystallizing membrane proteins for structure determination. The uptake of the method is such that it is experiencing what can only be described as explosive growth. This timely, comprehensive and up‐to‐date review introduces the reader to the practice of in meso crystallogenesis, to the associated challenges and to their solutions. A model of how crystallization comes about mechanistically is presented for a more rational approach to crystallization. The possible involvement of the lamellar and inverted hexagonal phases in crystallogenesis and the application of the method to water‐soluble, monotopic and lipid‐anchored proteins are addressed. How to set up trials manually and automatically with a robot is introduced with reference to open‐access online videos that provide a practical guide to all aspects of the method. These range from protein reconstitution to crystal harvesting from the hosting mesophase, which is noted for its viscosity and stickiness. The sponge phase, as an alternative medium in which to perform crystallization, is described. The compatibility of the method with additive lipids, detergents, precipitant‐screen components and materials carried along with the protein such as denaturants and reducing agents is considered. The powerful host and additive lipid‐screening strategies are described along with how samples that have low protein concentration and cell‐free expressed protein can be used. Assaying the protein reconstituted in the bilayer of the cubic phase for function is an important element of quality control and is detailed. Host lipid design for crystallization at low temperatures and for large proteins and complexes is outlined. Experimental phasing by heavy‐atom derivatization, soaking or co‐crystallization is routine and the approaches that have been implemented to date are described. An overview and a breakdown by family and function of the close to 200 published structures that have been obtained using in meso‐grown crystals are given. Recommendations for conducting the screening process to give a more productive outcome are summarized. The fact that the in meso method also works with soluble proteins should not be overlooked. Recent applications of the method for in situ serial crystallography at X‐ray free‐electron lasers and synchrotrons are described. The review ends with a view to the future and to the bright prospects for the method, which continues to contribute to our understanding of the molecular mechanisms of some of nature's most valued proteinaceous robots.